Impact of daily supplement of probiotic on the production performance of Akar Putra chickens - Jawad, Hasan S. A.; Idris, Lokman Hakim; Naji, Saad A.; Abu Bakar @ Zakaria, Md Zuki; Kasim, Azhar (Universiti Putra Malaysia Press, 2016)
This study was conducted to investigate the effects of prepared probiotic (PP) on the live body weight, weight gain, feed intake and feed conversion ratio in Malaysian chicken (Akar Putra). A total of 72 day-old Akar Putra chicks were reared for 12 weeks and randomly assigned to three dietary treatments (24 chicken/treatment), with 3 replications for each (8 chicken/replicate). The treatments consisted of a control group (T1), and the supplemented diet with probiotic in the second treatment was prepared at the rate 1:1 (1 kg of commercial broiler feed + 1 g PP). While the rate was 1:2 (1 kg of commercial broiler feed + 2 g PP) in the third treatment. Supplementing probiotic in both rates revealed significant improvement in terms of males' and females' growth rates, final live body weight, weight gain and feed conversion ratio. Based on the research findings, the best results were obtained when chickens received 1 g PP in males and 2 g in females.